THE EFFECTIVENESS OF THE FAMILY HOPE PROGRAM (PKH) ON THE WELFARE OF THE COMMUNITY OF DONGGALA KODI VILLAGE, ULUJADI DISTRICT - Asrit; Andi Herman Jaya; Edhi Taqwa; Armin; Laendatu Paembonan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The Family Hope Program (PKH) is a conditional social assistance policy designed to reduce poverty and improve community welfare by improving the quality of human resources. This study aims to analyze the effectiveness of the family hope program on the welfare of the Donggala Kodi Village community, Ulujadi District, from an economic aspect, especially in increasing income, as well as household expenditures for education and health, this research method uses a descriptive and qualitative approach through observation and interviews, the results of the study indicate that PKH contributes to the economic stability of poor households by helping to meet basic needs and reduce the burden of expenses. However, the economic effectiveness of the program still faces challenges in the form of dependence on assistance, inaccurate targeting, and limited impact on increasing productive income. Therefore, this study is important to provide an economic evaluation as a basis for formulating more efficient, targeted, and sustainable policies in efforts to alleviate poverty and improve community welfare.